Raul Seixas: um legado crítico e cultural - Marasca, Syro Fernando Fenerich [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This paper consists in doing a link between the life trajectory and the musical work of the brazilian singer and songwriter Raul Seixas, of the 1970s and 1980s, with the Brazilian History context of the second half of the twentieth century. From the biography of the artist, taking into account his personal trajectory together with his long musical career, this paper will also deal with theoretic discussions relevants to the History and Sociology studies, which are articulated with his musical productions done in the period of the 1970s and 1980s. The present research may become important in order to think about the past lived by the brazilian society, in the latter half of the twentieth century, and to demonstrate the cultural importance that Raul Seixas brought forth in this period

Este trabalho consiste em fazer uma conexão entre a trajetória de vida e a obra musical do cantor e compositor baiano Raul Seixas, das décadas de 1970 e 1980, com a História do Brasil, no período da segunda metade do século XX. A partir da biografia do artista, perpassando sua trajetória pessoal de vida em conjunto com sua longa carreira musical, esse trabalho também irá tratar sobre as discussões teóricas pertinentes às áreas da História e da Sociologia, que se articulam com sua produção musical gerada nas décadas de 1970 e 1980. A presente pesquisa pode se tornar importante para se pensar o passado que a sociedade brasileira vivenciou na segunda metade do século XX e demonstrar a importância cultural que Raul Seixas gerou durante esse período
Keywords: Seixas, Raul 1945-1989 Crítica e interpretação; Brasil - Historia - 1964-1985; Guerra fria; Contracultura; Música; Music